2018
DOI: 10.3390/ijms19082383
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic and Comparative Analyses of Complete Plastomes of Croomia and Stemona (Stemonaceae)

Abstract: The monocot genus Croomia (Stemonaceae) comprises three herbaceous perennial species that exhibit EA (Eastern Asian)–ENA (Eastern North American) disjunct distribution. However, due to the lack of effective genomic resources, its evolutionary history is still weakly resolved. In the present study, we conducted comparative analysis of the complete chloroplast (cp) genomes of three Croomia species and two Stemona species. These five cp genomes proved highly similar in overall size (154,407–155,261 bp), structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 67 publications
10
37
0
Order By: Relevance
“…The majority of the preferred codons (RSCU >1) ended with A or U, with the exception of UUG (RSCU = 1.25). This phenomenon is congruent with the results from other plant studies (Table S4) (Lu et al, 2018;Yi & Kim, 2012).…”
Section: Codon Usagesupporting
confidence: 93%
See 2 more Smart Citations
“…The majority of the preferred codons (RSCU >1) ended with A or U, with the exception of UUG (RSCU = 1.25). This phenomenon is congruent with the results from other plant studies (Table S4) (Lu et al, 2018;Yi & Kim, 2012).…”
Section: Codon Usagesupporting
confidence: 93%
“…IR regions are the most conserved regions in the cp genomes. Frequent expansions and contractions at the junctions of SSR and LSC with IRs illustrate the relationships among taxa and have been recognized as evolutionary signals (Khakhlova & Bock, 2006;Inkyu et al, 2018;Lu et al, 2018;Raubeson et al, 2007;Wang et al, 2008). In this study, only a few variations were found among the five Dicliptera species.…”
Section: Ir Expansion Analysismentioning
confidence: 63%
See 1 more Smart Citation
“…These results also prove that the IR regions were more conserved than the LSC and SSC regions, and the average value of Pi in the non-coding regions was more than three times as much as in the coding regions. Among these regions, ycf1, rps15, rpl22, infA, psbT-psbN, petD-rpoA, psaC-ndhE, ccsA-ndhD, ndhF-rpl32, and rpl32-ccsA have also been reported as highly variable regions in other plant species, such as Kaempferia species [23], Aristolochis species [26], orchid species [42], Lythraceae species [43], Quercus species [44], Lilium species [45], Croomia species [46], Stemona species [46], and Eucommia species [47]. The ndhF-rpl32 and ccsA-ndhD regions had been used as molecular markers for phylogenetic analyses [18,19].…”
Section: Divergence Hotspot Regions Analysesmentioning
confidence: 99%
“…Stemona japonica is important one of herb plant in China, which belongs to the genus Stemona the family Stemonaceae (Lu et al 2018). It is native to China, the Indian Subcontinent, Southeast Asia and northern Australia (Yang et al 2006).…”
mentioning
confidence: 99%